Reporting the Cases on Healing of Large Periapical Lesions by Non-surgical Approach - Bonny Paul; Kavita Dube (Highlights on Medicine and Medical Research Vol. 2, 2021)
Introduction: Periapical lesions generally develop as a sequel to pulpal infection. When there is a large periapical tendency visible on the radiograph, clinicians tend to have a surgical approach towards treatment. Most periapical lesions can be classified as abscess, granuloma or cysts. However a non- surgical approach with appropriate use of intracanal medicaments should be attempted to salvage teeth. This paper demonstrates healing of large periapical lesions in two cases by non – surgical Endodontic treatment. Case Presentation: This report describes Endodontic treatment of a mandibular first molar and maxillary incisors. Calcium hydroxide in an aqueous vehicle was placed as intracanal medicament, the dressing changed every fifteen days for a period of three months. Continued follow ups demonstrated radiographic healing and the patients were asymptomatic. Conclusion: The case reports presented in this article showed healing of large periapical lesions following endodontic treatment. Isolation with rubber dam, thorough chemo mechanical debridement of the root canal space with use of calcium hydroxide as intracanal medicament is emphasized. It is recommended to monitor radiographically the prognosis of a large periapical lesion following an orthograde endodontic therapy before the decision of performing a periapical surgery is contemplated.